Andy Warhol photography : the Andy Warhol Museum, Pittsburgh, Hamburg Kunsthalle - Warhol, Andy, 1928-1987.; Heinrich, Christoph; Breitz, Candice; Warhol, Andy, 1928-1987.; Hamburger Kunsthalle (Thalwil/Zürich ; New York : Edition Stemmle, 1999)
Catalog of the exhibition from May 13, 1999-Aug. 22, 1999 in the Hamburg Kunsthalle and Nov. 6, 1999-Feb. 15, 2000, the Andy Warhol Museum, Pittsburgh, Pa.
Foreword / Uwe M. Schneede -- Foreword / Thomas Sokolowski -- Andy Warhol -- Photography. Andy Warhol. Art Director -- Amateur -- Artist / Christoph Heinrich. Still Life: Andy Warhol's Photography as a Form of Metaphysics / Mark Francis. Hollywood Stars and Noble Savages: Andy Warhol's Photography Collection / John Smith. Andy Warhol, Photographic Tradition and Zeitgeist / Ludger Derenthal -- Stars and Disasters. Popular Photography / Margery King -- The Automatic Portrait. "It was the machine doing the work." Pictures from the Photobooth / Christoph Heinrich. Don't Worry. Everything Will be Splendid. Ethel Scull Talks about her Portrait. Brigitte Bardot, Jeanne Moreau, Marilyn Monroe -- All Packed in One. Holly Solomon Reminisces -- Film Stills -- Still Films. Freezing a Motion Picture. An Interview with Gerard Malanga. "Nagging Tunes You Can't Shake off." Repetitive Aspects of Andy Warhol's Work / Dorte Zbikowski -- The Image Factory. Sometime Around 1970, Andy Warhol Bought a Big Shot Camera. Vincent Fremont on Warhol's Polaroid Photographs. Jane Fonda Was Coming Down at 2:00 p.m. Excerpt from Andy Warhol's Diary, April 29, 1982. The Warhol Portrait: From Art to Business and Back Again / Candice Breitz -- The Making of the Self. "The Red Lobster's Beauty." Correction and Pain in the Art of Andy Warhol / Karin Schick -- Sex & Food & Photography. "Progress is very important and exciting in everything except food" / Reva Wolf -- Parties & People. "Oh when will I be famous, when will it happen?" Andy Warhol's Society Photos / Hubertus Butin -- Warhol Exposed. Biographical Notes on 16 Photographers / Heather Hess and Dorte Zbikowski. Leila Davies Singeles. Otto Fenn. Edward Wallowitch. Duane Michals. David McCabe. Billy Name. Stephen Shore. Nat Finkelstein. Brigid Berlin. Timm Rautert. Richard Avedon. Cecil Beaton. Bill King. Oliviero Toscani. Christopher Makos. Robert Mapplethorpe.
Catalog of the exhibition from May 13, 1999-Aug. 22, 1999 in the Hamburg Kunsthalle and Nov. 6, 1999-Feb. 15, 2000, the Andy Warhol Museum, Pittsburgh, Pa.
boek
Keywords: Warhol, Andy, -- 1928-1987 -- Exhibitions; Photography, Artistic -- Exhibitions; Portrait photography -- Exhibitions; Warhol, Andy, -- 1928-1987; Photography, Artistic; Portrait photography; Fotografie; Portretten; Exhibition catalogs